THE PERFORMANCE ANALYSIS OF MIDWIFERY SERVICES IN SAMARINDA CITY - Johan, Herni (STMIK Widya Cipta Dharma, 2023)
Antenatal care (ANC) was an essential part of healthcare services for pregnant women. Various studies showed that antenatal care could improve care experiences and health outcomes for pregnant women and newborns. This study aimed to analyze the factors influencing the performance of midwives in antenatal care services in Samarinda City. This research used a quantitative method with a cross-sectional approach. The respondents of the study were the entire population, totaling 23 people, and were obtained through a questionnaire. Data processing was done with SPSS and data analysis used statistical tests, including univariate, bivariate, and multivariate analyses. The results of the study showed that there was a relationship between age, employee status, and years of service with the performance of midwives in ANC services. This study recommended that the Health Department and midwives establish human resource management policies for midwives with non-permanent employee status and regulate incentives that could improve performance in ANC services. Additionally, it was important to carry out antenatal care with full responsibility and seriousness, considering that these services were related to the Maternal and Child Health program that needed to be achieved.